Isolation of hydrogen from water and its utilization as a co-fuel for trucks into fuel-efficient vehicles - Kradang-nga, Sittichot; Kachapongkun, Pongsakorn; Chowwanonthapunya, Thee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This research focused on the separation of hydrogen gas from water and its utilization as a supplementary fuel blended with the primary fuel of an internal combustion engine. The test was divided into two steps: evaluating the energy efficiency of the electrolyzer and conducting experiments on pickup trucks (common rail diesel engine, 2,499 cc) to determine energy savings and pollution emission. The results showed that the efficiency of the electrolysis system with an average electricity consumption of 125.74 W was 84.83 kWh/kgH2 and the theoretical efficiency of the electrolyzer in separating hydrogen gas from water was 45.97%. Results from the test on a pickup truck using 100% diesel fuel and hydrogen-diesel dual fuel with loads of 1,850 and 2,100 kg over a distance of 11 km showed that using a hydrogen-diesel dual system resulted in fuel savings of 27.8% and 16.70%, as compared to that of using pure diesel fuel system. Besides, levels of black smoke, PM2.5, and PM10 of the hydrogen-diesel dual fuel system were lower than those of the pure diesel fuel system.